Revisión del proceso de la administración estratégica, estudio del paradigma de estrategia, estructura y equifinalidad: Una investigación empírica en empresas del noreste de Mexico (Review of the strategic management process, study of the strategy, structure and equifinality paradigm: An empirical research in northeastern Mexican companies) - Aguirre, H.; Flores, O.; Alatorre González, Victoriano Francisco (Facultad de Contaduría Pública y Administración U.A.N.L., 2008)
Abstract. The objective of this research is to test empirically the strategy, structure and equifinality paradigm in northeast México companies. Businesses, in this region of the country, were studied through the application of a questionnaire. The paradigm of Chandler regarding “structure follows strategy” is the independent variable. The dependent variable is established as finding equifinal results with or without the presence of the strategy-structure paradigm. From this study, two contributions materialize. The first one is that it is effectively true the relationship between strategy and structure. The second and more important one is that the equifinality paradigm was in fact true and empirical evidence was obtained. To determine the reasons for the functioning of this paradigm, more research is needed. “No matter the beginnings”, final success may be explained by the wholistic nature of management. Resumen. Esta investigación busca comprobar empíricamente el paradigma entre estrategiaestructura y equifinalidad en empresas del noreste de México. Se llevó al cabo un estudio a través de la aplicación de cuestionarios a negocios de esa parte del país. Se consideró como variable independiente la existencia del modelo de Chandler acerca de que la “estructura organizacional sigue a la estrategia”. La variable dependiente, se establece como la obtención de resultados equifinales (igualmente finales), con o sin la existencia del paradigma de estrategia-estructura. Dos contribuciones emergen de este estudio. La primera consiste en haber encontrado que efectivamente existe una relación entre estrategia y estructura en las empresas investigadas. La segunda, y más importante, es que se evidenció, con prueba empírica, el paradigma de equifinalidad.